IDENTIFICATION OF INFORMATION AND COMMUNICATION COMPETENCES - Oleksandr M. Kryvonos (Інформаційні технології і засоби навчання, 2010)
Article is devoted to identification of information and communication competence and levels of their formation of the future teachers of informatics. It examines the different approaches to the problem of criteria for evaluating competence, describes the formation of the main levels of information and communication competence. Also it has been presented partial results of a survey which was conducted among students of the second year of training on specialties "Information", "Mathematics and the foundations of computer science", "Physics and the foundations of computer science" in Physics and Mathematics at the Zhytomyr State University named after Ivan Franko.